Who Cares (For Whom)? - Spangenberg, Joachim H.; Lorek, Sylvia (Frontiers in Sustainability, 2022)
The debate about care has intensified in the Covid-19 crisis. A consensus appears to be emerging that care work - mostly provided by women - is not only essential to our societies, but also undervalued, reputationally as well as - for the paid work - regarding its remuneration. As care is essential for the cohesion of societies, there is an urgent need to improve the situation. However, care comes in too many forms for general recommendations for improving the situation to be effective. Its majority in terms of working hours is unpaid, but the paid part of it in health, caring or education, is indispensable for any society built upon a division of labour. Finally, not every activity is work, and not every work is care - thus leisure activities are not necessarily care work. Care can be motivated by a plethora of reasons, and take a diversity of forms. To allow for effective suggestions for improvement, we systematically distinguish different classes of care. The first is caring for oneself, be it in terms of health care, hygiene, or the self-production of consumer goods, both short and long lived. The second is caring for the family (native and chosen family including friends). It again includes caring for their health, but also their household (either the common one, or the one the caretaker is managing for the care receiver). Extending the reach of care even wider, we come to care for the public good, with the community from village or city district to higher levels being the beneficiaries. This includes the volunteers working with environment, development, feminist, trade unions, food banks or belief organisations. Finally, there are professional care activities where financial benefit is involved. We observe a permanent process of substituting exchange value oriented care work for voluntary, use value based care, and vice versa. Such trends, however, are no destiny; they can be shaped by political interventions. Whether or not a professional or voluntary approach is preferable, depends on the assessment criteria applied which in turn represent political, ethical and cultural preferences.